Uma sequência didática para o ensino de conceitos em probabilidade e estatística - Rosa, Bruno Castilho (2023)
The study of Probability and Statistics in both primary and secondary education has been the subject of research in recent years. One of the challenges for many students in this area is to learn basic concepts, although this topic is mandatory in the initial grades of the educational process. To solve this problem, we present in this work a didactic sequence based on Guy Brousseau’s theory of didactic situations, which includes several activities related to the basic concepts of probability and statistics such as randomness, equiprobability, dependent and independent events, and so on. The proposed didactic sequence contemplates specific situations organized in a teaching-learning sequence based on the principle of instructional design (ID). This involves an iterative process of design, implementation and redesign of the didactic sequence. The proposed situations were included in an educational product entitled "Teaching of Probability and Statistics through Experiments". The results we obtained allowed us to identify the main difficulties faced by the test subjects. In addition, the results showed that the proposed didactic sequence contributed to the understanding and articulation of the concepts studied in the areas of probability and statistics.